Enabling Power Beacons and Wireless Power Transfers for Non-Orthogonal Multiple Access Networks - Chi-Bao Le; Nhan Duc Nguyen (Journal of Telecommunications and Information Technology, 2021)
This paper studies downlink cellular networks relying on non-orthogonal multiple access (NOMA). Specifically, the access point (AP) is able to harvest wireless power from the power beacon (PB). In the context of an AP facilitated with multiple antennas, the transmit antenna selection procedure is performed to process the downlink signal, with the transmission guaranteed by energy harvesting. Therefore, a wireless power transfer-based network is introduced to overcome power outages at the AP. In particular, an energy-constrained AP harvests energy from the radio frequency signals transmitted by the PB in order to assist in transmitting user data. Outage performance and ergodic capacity are evaluated with the use of closed-form expressions. In order to highlight some insights, approximate computations are provided. Finally, numerical simulations are performed to confirm the benefits of combining the downlink NOMA transmission and the transmit power scheme at the AP in order to serve a multitude of users